Updates from Helen Keller International’s efforts in OFSP dissemination - International Potato Center (2016)
A multi-sectoral approach is key for large scale dissemination and adoption of orange-fleshed sweetpotato (OFSP) and harnessing its nutritional potential. This requires creating demand for OFSP by communicating the nutritional and agronomic advantages, while at the same time providing training on the cultivation, storage and processing.